(untitled) (PANGEEA, 2025)
Currently, soil pollution is a critical environmental problem that concerned all humanity due to its impact on ecological environment and human health. In order to remediate the contaminated soils, some technologies, generally based on physical, chemical, thermal, and biological processes, have long been in use. However, effectiveness of these methods depends considerably on soil type and characteristics, level of pollution and mixed contaminants present in soil. Therefore, in the present study, the pedological properties of the soil collected from abandoned mining perimeter of Larga de Sus from Zlatna (Alba County, Romania) were investigated in order to choose the most appropriate method for soil remediation and establish the parameters of soil remediation technology. The results indicated that soil in the area is highly acidic which favors the mobility of heavy metals in soil and other environmental components. On the other hand, most of the samples are partially structured and poorly structured while some samples are well structured, very poorly structured, or present a lack of aggregates structure. Also, the coarse sandy and loam-sandy texture of the samples was identified. Thus, considering soil properties, soil washing technology may be the appropriate remediation technology for contaminated soil in the studied area considering costs and efficiency.